A sustained high fat diet for two years decreases IgM and IL-1 beta in ageing Wistar rats. Issue 1 (December 2015) - Pongratz, Georg; Lowin, Torsten; Kob, Robert; Buettner, Roland; Bertsch, Thomas; Bollheimer, L.
Abstract Background The immune system undergoes several alterations of innate and adaptive immunity during ageing. The main features of the aged immune system are a reduced diversity of T cell receptors and a reduced activity of innate immune cells with subsequent changes in adaptive immunity resulting in a less effective, less specific, and dys-regulated immune response and in an increased susceptibility towards infection, malignancy, and autoimmunity. The process is referred to as immunosenescence and is also modulated by environmental modifiers, such as dietary factors. High fat diet (HFD), via direct modulation of immune cell function by fatty acids and/or increased body fat mass, influences immune function. However, it is not clear whether HFD is beneficial or detrimental for the functioning of the ageing immune system. Methods Male Wistar rats fed with either a high fat diet (HFD 43 en% of fat) or control diet (SD, 25 en% of fat) over up to 24 month and were analyzed for plasma IL-1β, IL-6, TNF, IgM, IgG1, IgA, IgG2a, IgG2b, IgG2c, light chains lambda and kappa, testosterone, prolactin and percentage of splenic B cells and apoptosis rate, respectively. Results In general, all analyzed immunoglobuline isotypes increased with age, except for IgA. This increase was attenuated by HFD. In HFD and SD rats the percentage of B cells in the spleen and also their apoptotic rate was lower in aged as compared to young animals with no additional diet-induced effect. Testosterone and prolactin levels were lower in old animals, as expected. There was a statistical trend towards an increased prolactin/testosterone ratio in middle aged (6–12 monthsnth) HFD rats as compared to SD. IL-6 was neither affected by HFD nor age. On the other hand, HFD rats showed a decrease in IL-1β as compared to SD, which correlated with the above-mentioned suppressive effect on immunoglobulin isotypes, especially IgM. Conclusion In Wistar rats, HFD reveals an immunosuppressive effect in ageing animals by decreasing immunoglobulins, especially IgM, and IL-1β when compared to SD.